Carotid Artery Vascular Mechanics Serve as Biomarkers of Cognitive Dysfunction in Aortic‐Banded Miniature Swine That Can Be Treated With an Exercise Intervention. Issue 5 (May 2016) - Olver, T. Dylan; Klakotskaia, Diana; Ferguson, Brian S.; Hiemstra, Jessica A.; Schachtman, Todd R.; Laughlin, M. Harold; Emter, Craig A.
Abstract : Background: Cognitive impairment in the setting of heart failure with preserved ejection fraction remains poorly understood. Using aortic‐banded miniature swine displaying pathological features of human heart failure with preserved ejection fraction, we tested the hypothesis that increased carotid artery stiffness and altered carotid blood flow control are associated with impaired memory independent of decreased cardiac output. Furthermore, we hypothesized that chronic exercise prevents carotid artery vascular restructuring and preserves normal blood flow control and cognition in heart failure with preserved ejection fraction. Methods and Results: Yucatan pigs aged 8 months were divided into 3 groups: control (n=7), aortic‐banded sedentary (n=7), and aortic‐banded exercise trained (n=7). At 6 months following aortic‐banded or control conditions, memory was evaluated using a spatial hole‐board task. Carotid artery vascular mechanics and blood flow were assessed at rest, and blood flow control was examined during transient vena cava occlusion. Independent of decreased cardiac output, the aortic‐banded group exhibited impaired memory that was associated with carotid artery vascular stiffening, elevated carotid artery vascular resistance, and exaggerated reductions in carotid artery blood flow during vena cava occlusion. Chronic exercise augmented memory scores, normalized blood flow control, and improved indices of carotid artery vascular stiffening. Indices of vascular stiffening were significantly correlated with average memory score. Conclusions: Carotid artery stiffness and altered vasomotor control correlate with impaired cognition independent of cardiac systolic dysfunction. Carotid artery vascular mechanics may serve as a biomarker for vascular cognitive impairment in heart failure with preserved ejection fraction. Chronic low‐intensity exercise reduces vascular stiffening and improves cognition, highlighting the utility of exercise therapy for treating vascular cognitive impairment in heart failure with preserved ejection fraction.